A tributação das operações de comércio eletrónico - Martins, Carlos Jorge Fernandes Antunes (2016)
The main aim of the following project is to analyze the operations of electronic commerce from a tax point of view in tax area, namely the business to business and business to consumer transactions. The development of the electronic commerce tore down geographical boundaries and, as a result, most of the commercial transactions are now processed via internet. Hence, the way commercial transactions are done are changing, which raised issues in the tax area, particularly on how these transactions should be taxed. Both the OECD and the European Commission have been developing and defining the main policies to better legislate the electronic commerce. In order to enrich this master thesis, several proposals of taxation on e-commerce are presented, by means of assembling some authors’ perspectives, thus trying to get to a consensus. We got to the conclusion that the same principles that exist in traditional commerce should be applied to the electronic commerce. However, some concepts should be clarified specifically the permanent establishment. The latest developments in the European Union as far as e-commerce is concerned, proved to be game changing. With the One Stop Shop’s creation, organizations have today a valid alternative to the traditional VAT registration in order to fulfill their tax obligations.